Postmodernism and the need for story and promise: how Robert Jenson's theology addresses some postmodern challenges to faith - A. H. Verhoef (Acta Theologica)
Modernity’s belief that we live in a narratable world (a world with a story) and its confidence in progress (a world with a promise), are terminated by postmodernism’s insights. This is how the American Lutheran theologian Robert Jenson understands the impact of postmodernism. If this is true, it poses great challenges for the Christian faith to be communicated and accepted within this context. This article assesses how Jenson’s theology attempts to address postmodernism’s need for a new story and promise. It concludes that Jenson’s theology, as a Trinitarian theology, forms a coherent answer to these challenges because it is a narrative and eschatological theology. This article indicates, amongst other things the importance of Jenson’s understanding in his theology of the relation between God and time. The significance of Jenson’s approach is that it, firstly, understands the church as a narratable world, with a visible promise, and that it, secondly, follows a  characteristically postmodern methodology in addressing these challenges.